Effects of Age and Middle Ear on the Frequency Tuning of the cVEMP and oVEMP - Jha, Raghav Hira; Piker, Erin G.; Romero, Daniel (Journal of the American Academy of Audiology, 2022)
Background Upward shift in the air conducted (AC) frequency tuning of vestibular evoked myogenic potentials (VEMPs) as an effect of aging is hypothesized to be due to the microstructural stiffening changes in the inner ear. However, with an AC stimulus, it may be possible that the shift in the frequency tuning of VEMPs as an effect of aging may also be due to contributions from the middle ear.Purpose The main aim of this study was to examine the effects of age on the frequency tuning of the cervical VEMP (cVEMP) and ocular VEMP (oVEMP) and determine the role of middle ear transmission characteristics in shaping these effects.Research Design Standard group comparison.Study Sample One-hundred seven participants divided in three groups: young adult, middle-age, and older adults with “normal” middle ear and negative history of neurological or vestibular complaints.Data Collection and Analyses Middle ear measures included static admittance and middle ear resonant frequency. cVEMP and oVEMPs were elicited with AC tone bursts at 500, 750, and 1,000 Hz.Results No significant effect of age was observed on any of the middle ear measures. There was a significant effect of age on the amplitude of the cVEMP, but this effect was frequency specific. The age-related reduction in cVEMP corrected amplitude was only observed when the eliciting stimulus was 500 or 750 Hz, with no significant effect observed with a 1,000 Hz stimulus. For the oVEMP, the effects of age were apparent at all stimulus frequencies. We also observed a general upward shift in the frequency tuning of both the cVEMP and oVEMP for middle-age and older adults, with 750 and 1,000 Hz yielding higher response rates and larger amplitudes among middle-aged and older adults. Measurements of middle ear did not significantly contribute to the observed findings.Conclusions The upward shift in frequency tuning of VEMPs among middle age and older adults could be due to the changes in the vestibular system and not from the middle ear. These results support the use of different frequency stimuli (i.e., 750 or 1,000 Hz) to elicit a VEMP if a response is absent using a 500 Hz stimulus, especially in patients over the age of 40.
Keywords: aging; cVEMP; oVEMP; middle ear resonant frequency